Characterization of cavity dwelling honey bees using enzyme polymorphism - Kumar, Rajeev; Kumar, Neelima R (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> The most intensively studied of all insects are perhaps honey bees. Recognition of valid honey bee species has been difficult for several reasons. Most important reason has been the movement of honey bees all over the world for bee keeping which has resulted in their hybridization. Another problem is that scientists and bee keepers do not always use the same criteria for identification. While scientists are concerned with the biological parameters, bee keepers are more interested in behavioral traits. Even within a single species there are locally adapted populations called geographic ecotypes, which differ from each other in several morphological, biological, molecular and economic characteristics. Beside behavioral, morphological and cytogenetic evidence, electrophoretic data provide strong support for phylogenetic relationships among insects. Apis cerana and Apis mellifera are the Eastern and the Western cavity dwelling honey bees. Their habit of nesting in dark, enclosed spaces made it possible for man to domesticate them and to use them as a highly commercial industrial enterprise. A. mellifera is thought to have originated in the African tropics or Asia and colder European climates. The recent movement of bees by European settlers for bee keeping has resulted not only in worldwide distribution of Apis mellifera but has also led to some degree of hybridization between subspecies. On the other hand there has also occurred isolation of populations either by distance or by barrier giving rises to newer subspecies or races. To differentiate these honey bees on the basis of biochemical polymorphism alcohol dehydrogenase provided significant results and was observed to be an additional marker for the species.